Antimicrobial effect of photodynamic therapy versus laser therapy on Porphyromone gingivalis: In vitro study - Gordillo Caizaluisa, Daniela Carolina (2018)
At present there are different applications of the laser in Dentistry; This Therapy is based on the emission of luminous energy with different wavelengths. Depending on the procedure performed, they generate physical and chemical effects that produce biological and therapeutic responses such as wound healing, analgesic and anti-inflammatory effects, as well as inhibiting the progression of gingivitis and periodontitis. Objective: To evaluate the antimicrobial effect of Photodynamic Therapy (PDT) and Laser Therapy on colonies of Porphyromona Gingivalis (Pg). Materials and Methods: Experimental study, in vitro. The sample consisted of 48 solutions of (Pg) that approx. contains 1000 colonies, were divided into 6 groups of 8 samples each being: G1: 0.05% Methylene blue AM + led light, G2: 0.1% AM + led light, G3: 0.05% AM + Laser, G4: 0.1% AM + Laser, G5 Laser Therapy (30 “) and G6: Laser Therapy (60”). The data obtained were statistically analyzed by the Mann Whitney U test with a level of significance of 5%. Results: The mean cfu values were 190.1, 187.8, 23.6, 13.1, 2.1 and 0.0 for G1, G2, G3, G4, G5 and G6 respectively. obtained a Significance (p <0.001) that allowed us to infer that the antimicrobial capacity was different for the different protocols used. Conclusion: The PDT with laser and the use of the laser were more effective than the PDT with led light in the reduction of bacterial colonies (Pg).